When Students are Consumers: Reflections on Teaching a First-Year Gender Course (That is Not a Gender Studies Course) - Dowsett, Julie E. (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
This paper considers my experiences teaching a first-year course, Gender and the Law, at York University. I situate these experiences in the context of the corporatization of universities under neoliberalism, and the scholarly literature on gender, race, and course evaluations. I contend that many students are disengaged and alienated, viewing themselves as consumers and me as a service provider. I outline some of my pedagogical strategies that attempt to disrupt student mindsets and promote engagement.